Accessibility of green spaces in a metropolitan network using space syntax to objectively evaluate the spatial locations of parks and promenades in Doha, State of Qatar - Heba O. Tannous (16810707) (2021)
Accessibility indicates the ease of reaching many destinations from many origins in the urban network at various scales of space. It plays an important role in determining the location of public facilities to maximize usability for a large population or limit use to a smaller community. The absence of urban green spaces is a notable consequence of rapid urbanization in many cities around the world. Doha in the State of Qatar is no different, where rapid urban expansion and globalization has a significant impact on the quality and quantity of green spaces available. This paper analyzes the location and size of public parks, promenades, and other green spaces in Doha in terms of their accessibility. Do they follow a discernible spatial logic in terms of their size and accessibility linked to the design intent of public planning policies? The research shows there is spatial and social logic to the physical and spatial characteristics of open green spaces in Doha above a certain size. In contrast, those characteristics in smaller examples tend to be more random, mainly due to issues of land availability and amenity provision in private developments. Other Information Published in: Urban Forestry & Urban Greening License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ufug.2020.126892